2022
DOI: 10.1590/fst.71621
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological, chemical, fatty acid and antioxidant characteristics of goat milk kefir enriched with Moringa oleifera leaf powder during storage

Abstract: Fortification of compounds that contain functional components can improve product quality without affecting the product characteristics in the storage. This study evaluated the effect of supplementing Moringa leaf powder (0; 0.5; 1.0; 1.5; 2.0% w/w) and different storage periods (0, 7, and 14 days) on the quality of goat milk kefir. The observed parameters were microbiological characteristics (total lactic acid bacteria (LAB), total plate count or TPC, total yeast) chemical characteristics (total solids, acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
3
2
3
Order By: Relevance
“…The addition of Lacticaseibacillus casei AP, oat milk, or both, and kefir storage time have significantly (P<0.05) increased alcohol content. Similarly, the alcohol content of kefir enriched with Moringa oleifera leaves increased with storage life (Wulansari et al, 2022a). Kefir produced from red rice milk and Lactobacillus bulgaricus dan Candida kefir starter produced kefir that contained an average of 1.5% (Sulistyaningtyas et al, 2019), higher than that reported in the present study with an average of 0.44%.…”
Section: Physicochemical Analysiscontrasting
confidence: 73%
See 1 more Smart Citation
“…The addition of Lacticaseibacillus casei AP, oat milk, or both, and kefir storage time have significantly (P<0.05) increased alcohol content. Similarly, the alcohol content of kefir enriched with Moringa oleifera leaves increased with storage life (Wulansari et al, 2022a). Kefir produced from red rice milk and Lactobacillus bulgaricus dan Candida kefir starter produced kefir that contained an average of 1.5% (Sulistyaningtyas et al, 2019), higher than that reported in the present study with an average of 0.44%.…”
Section: Physicochemical Analysiscontrasting
confidence: 73%
“…In the first stage, the culture starter was prepared by heating goat milk at 85 °C for 30 min, then cooling to room temperature. After that, 3% kefir grain was incorporated into the milk and allowed incubation for 18 h at room temperature (Wulansari et al, 2022a). After fermentation, the milk was strained to collect the kefir grains, or the kefir starter, which would be added at the stage of sample production.…”
Section: Production Of Starter Cultures Of Kefirmentioning
confidence: 99%
“…The kefir in this study had pH of 4.19, which was not significantly different from the pH value of 4.31 recorded for kefir made using a combination of cow's and oat milk (Dinkçi et al, 2015) and kefir added with inconventional sugar was 4.4 (Larosa et al, 2021a). The kefir's acidity level in the present study was 2.12%, which is higher than the value of 0.87% previously (Wulansari et al, 2021), but conforms to the standard acidity indicated in Dinkçi et al (2015), which is a minimum of 0.60%. The pH value and acidity level measured in this study showed that the combined addition of oat milk and L. casei AP did not affect the acidity level of the kefir product.…”
Section: Physicochemical Quality Of Kefircontrasting
confidence: 72%
“…It was positively correlated with data in Table 2, where higher oat milk concentrations resulted in lower water contents. The mean water content value obtained in the present study was 86.48%, which is not significantly different from the previously reported values of 82.61% (Wulansari et al, 2021), 87.91% (Cais-Sokolińska et al, 2015, 87.33% (Nurliyani et al, 2015), and 87.63 (Satir & Guzel-Seydim, 2016). A high total solid content is expected to reduce syneresis, which negatively affects nutrition and sensory qualities (Barukčić et al, 2017).…”
Section: Physicochemical Quality Of Kefircontrasting
confidence: 69%
“…There is a growing development of dairy goat products, such as yogurts, dairy drinks, and cheeses, as a way of masking the characteristic goat milk flavor and turning its derivative goods more attractive. Studies have evaluated, for example, the use of plant extracts such as quinoa extract (El-Shafei et al, 2020), Pistacia atlantica resin (Hadjimbei et al, 2020) and Moringa oleifera leaf powder (Wulansari et al, 2022), to improve the sensory and technological properties of fermented goat milk, as well as the addition of probiotic microorganisms, which, in addition to making the food functional, can release compounds that contribute to the aroma and flavor of the final product (Ranadheera et al, 2019). In addition to it, the increased demand for hypoallergenic and functional food is also contributing to the expansion of this field, mainly for yogurt production (Ranadheera et al, 2019;Ranadheera et al, 2018).…”
Section: Introductionmentioning
confidence: 99%